2022
DOI: 10.1007/s00705-021-05325-2
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of a novel secovirid infecting cassava in the Americas

Abstract: We report the complete genome sequence of a field isolate of a novel bipartite secovirid infecting cassava in Colombia, provisionally named "cassava torrado-like virus" (CsTLV). The genome sequence was obtained using Oxford Nanopore Technology, and the 5’ ends were confirmed by RACE. The RNA1 is 7252 nucleotides (nt) long, encoding a polyprotein of 2336 amino acids (aa) containing the typical “replication block”, conserved torradovirus motifs, and a Maf/Ham1 domain, which is not commonly found in viral genomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“… 2020 , Leiva et al . 2022 ), as well as in bacteriophages and giant DNA viruses (Kiljunen et al . 2005 , Deeg, Chow and Suttle 2018 , Sun and Ku 2021 ).…”
Section: Diversity and Evolution Of Non-core Modulesmentioning
confidence: 99%
“… 2020 , Leiva et al . 2022 ), as well as in bacteriophages and giant DNA viruses (Kiljunen et al . 2005 , Deeg, Chow and Suttle 2018 , Sun and Ku 2021 ).…”
Section: Diversity and Evolution Of Non-core Modulesmentioning
confidence: 99%
“…As it has been recently reported that plant viruses infecting Euphorbiaceae and especially Manihot esculenta (commonly known as Cassava) possess a homologue of ITPA (James et al, 2021; Leiva et al, 2022), we were curious whether ITP and IDP concentrations change during infection with such a virus. We chose to investigate this question in N. benthamiana because Arabidopsis is not a known host of viruses encoding ITPA.…”
Section: Resultsmentioning
confidence: 99%
“…After its first report in the south of Colombia, in the 1970s, the characteristic root symptoms of the disease have been reported in all the main Colombian regions where cassava is grown [ 1 , 11 , 15 , 26 ]. Here, it is worth mentioning that during surveys in the North Coast of Colombia in the early 1990s, root symptoms of CFSD were also associated with leaf mosaic symptoms, probably due to Secundina being at the time a popular genotype grown in this region.…”
Section: Symptoms Transmission and Geographical Distributionmentioning
confidence: 99%
“…As mentioned above, isolation by mechanical inoculation is not possible for most of these pathogens, and its common occurrence in mixed infections makes it harder to evaluate its individual or combined effect on cassava. Recently, Leiva et al [ 26 ] reported the occurrence of CsTLV in mixed infections with phytoplasma in fields with a high incidence of CFSD in the Department of Casanare (eastern Colombia). Several years of experience working with these pathogens have validated mechanical isolation in Nicotiana benthamiana plants, only for CsCMV and CsVX, which are not associated with root symptoms of CFSD.…”
Section: Cfsd-associated Pathogens and Molecular Diagnosticsmentioning
confidence: 99%